Substituting Sargassum sp. Compost for Inorganic Fertilizer Improves the Growth and Yield of Shallot (Allium cepa L. Aggregatum Group) - Muarif, Samsul (Universiti Putra Malaysia, 2022)
Fertilizers derived from natural materials, such as Sargassum sp. (seaweed), are a promising technique to overcome the negative impact of overuse of inorganic fertilizers. Groundwater contamination, soil degradation, and changes in the soil microorganism community are problems related to overdosing on inorganic fertilizer during crop production. The use of Sargassum compost (SC) as a substitute inorganic fertilizer was tested by evaluating the growth and yield of shallot grown on sandy soil. The research was arranged in a randomized complete block design consisting of four treatments and three blocks of replications. The treatments involved substituting SC for inorganic fertilizer, which were 100 inorganic, 25 SC + 75 inorganic, 50 SC + 50 inorganic, and 75 SC + 25 inorganic, respectively. The compositions of nitrogen (N), phosphorus (P), potassium (K), sodium (Na), sulfur (S), auxin, gibberellin, cytokinin, and kinetin in SC, as well as the growth and yield of shallot, were analyzed by analysis of variance followed by the least significant difference test. The results showed that the SC contained high organic matter (45.78), nitrogen (4.1), phosphate (0.5), potassium (0.8), sodium (7.2), sulfur (0.2), and plant growth hormones, such as auxin (8.14 mg.g−1), gibberellin (15.97 mg.g−1), cytokinin (7.70 mg.g−1), and kinetin (2.78 mg.g−1). Interestingly, all substitution levels of the SC for inorganic fertilizer improved nutrient absorption in the leaves, roots, and bulbs. Moreover, the growth and yield of shallot were not significantly different among the treatments. Therefore, to provide sufficient nutrients and growth hormones, SC could be substituted for up to 75 of organic fertilizers for shallot plants. © Universiti Putra Malaysia Press.